The Potential of selected Bornean bufonids (amphibian anuran bufonidae) as biological dressing in wound healing management - Suzila, Anak Bamic (Universiti Malaysia Sarawak, UNIMAS, 2013)
This study was conducted to assess the wound healing potential of selected species in family Bufonidae. The assessment of the healing process was compared with the normal dressing wound by using dH2O and the untreated wound. The study was conducted on day 3, day 7 and day 14. Three laboratory rats were utilised for each day of the experiment, for the purpose of the study. Ruler measurement data were collected and histological study were done. Histological sections of the skin specimens were stained by hematoxylin and eosin. Ruler measurement data suggested that the wound treated with skin Ansonia spinulifer healed faster than Phrynoidis juxtasper. However, histological evaluation suggested that both species A. spinulifer and P. juxtasper could not be justified their healing potential due to some limitations, such as no replication of the experiment, difficulty in handling the rats and error during analysing the histological slides.